The in-vitro antibacterial activity of Plectranthus scutellarioides (L.) R.BR. ethanolic leaf extract against bacteria associated with peri-implantitis / Nor Amiyah Bismelah - Bismelah, Nor Amiyah (2022)
Chlorhexidine is often used commercially in oral rinses for adjunctive treatment in peri-implantitis. However, it is not recommended for daily regime due to common side effects such as taste alteration and staining. Hence, the need for an alternative remedy with reduced side effects and suitable for long term use. The present study investigates Plectranthus scutellarioides (L.) R.Br. ethanolic leaf extract as potential antibacterial oral rinse against peri-implantitis that involve both early bacteria colonizers as well as the late bacteria colonizers. The study involved phytochemical screening of the ethanolic crystallized extract of Plectranthus scutellarioides (L.) R.Br. using mass-based identification to identify the presence of chemical constituent. The ethanolic extract was then screened for its antibacterial activity against the early colonizer’s bacteria namely Staphylococcus aureus, Streptococcus mitis, Streptococcus sanguinis, Streptococcus salivarius, Streptococcus oralis and Actinomyces viscosus as well the late colonizer bacteria namely, Aggregatibacter actinomycetemcomitants, Porphyromonas gingivalis, Treponema denticola, Prevotella intermedia, and Tanerella forsynthia using disc diffusion method. The ethanolic extract was subsequently tested for minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) as well as for its cytotoxicity effects on human gingival fibroblast cell (HnGF). The ultrastructural bacteria morphological changes were examined by scanning electron microscopy (SEM). Four flavonoid compounds were identified from Plectranthus scutellarioides (L.) R.Br. ethanolic extract, namely quercetin-3-glucoside, quercitrin, quercetin 3-(6''- acetylglucoside) and quercetin 3-O-acetyl-rhamnoside. The sensitivity test revealed that Plectranthus scutellarioides (L.) R.Br. ethanolic extract was effective against all the bacteria tested. MIC concentrations for the early colonizers were in the range of 1.56-12.50 mg/ml, and the MBC concentrations were within 3.13-12.5 mg/ml. For the late colonizers, the MIC concentration were within 3.13-12.50 mg/ml and MBC within 6.25-200 mg/ml. The ethanolic extract did not have any cytotoxic effect on HnGF cells at the tested concentrations within all three time periods (24, 48 and 72 hours). SEM images showed bacterial cell wall disruption for all the bacteria tested. The results showed that Plectranthus scutellarioides (L.) R.Br. ethanolic extract exerts its antibacterial property by disrupting the cell wall of all the bacteria tested. In conclusion, Plectranthus scutellarioides (L.) R.Br. ethanolic extract exerted its antibacterial activity property by disrupting the cell wall of the early and late bacteria colonizers of peri-implantitis. Hence, Plectranthus scutellarioides (L.) R.Br. ethanolic extract may be recommended for use as oral rinse for adjunctive treatment of peri-implantitis subjected to further study of its safety